Content-based video analysis, indexing and classification - Yuan, Yuming. (2008)
In this digital multimedia information era, in addition to traditional solutions for textual information, novel tools and systems are required to efficiently analyze, access and search the ever-growing multimedia materials. Actually, content-based video indexing and retrieval has become a very active research field during the past decade. Usually, video analysis, indexing, representation, browsing, retrieval are major components for accessing video content.